Footprints of obliquely incident internal solitary waves and internal tides near the shelf break in the northern South China Sea. Issue 12 (15th December 2016) - Ma, Xiaochuan; Yan, Jun; Hou, Yijun; Lin, Feilong; Zheng, Xufeng
Abstract: A mooring system and two sites of bottom currents were deployed over the slope and near the shelf break on the propagating paths of internal solitary waves (ISWs), west off Dongsha Atoll in the northern South China Sea. Data indicated that energetic ISWs obliquely shoaled onto the shelf west off Dongsha Atoll in an approximately 290° direction, causing strong reversing currents (some exceeding 80 cm/s) near the bottom. Two types of sandwaves and short scour channels are discernible on the seafloor near the shelf break, which have reasonable correlations with the obliquely incident ISWs and internal tides. Type 1 sandwaves, featured by ISWs at the depths of 130–150 m, have flat crests interacting with the isobaths at an angle of nearly 45° which slightly incline and migrate upslope. Type 2 sandwaves are associated with internal tides, which have crests parallel to the isobaths and distinctly incline and migrate downslope. Short channels are parallel to the depth contours and truncate the strata, which could be formed and maintained by along‐slope currents that are probably produced by the obliquely ISWs on a large gradient (γ > 0.8°). The ISWs can move coarse grains or suspend fine grains but do not change the long‐term trend of sediment transport on the seabed with larger gradients (γ/c > 1), which is dominated by internal tides. These features are likely widespread near the shelf break in the northern South China Sea and other seas but are limited on mild slopes where ISWs do not break. Key Points: Energetic obliquely incident ISWs generate extremely strong bottom currents exceeding 80 cm/s near the shelf break west of Dongsha Atoll Two types of sandwaves and short scour channels generate under obliquely incident ISWs and internal tides Obliquely incident ISWs feature sandwaves with flat crests and enhance sediment transports but cannot change the long‐term trend